Assessing the effectiveness of the Academic Workload Allocation Model at a South African Business School - Arendse, Linzee (School of Management Studies, 2022)
Managing workload allocation to ensure fairness and equity amongst staff can be a challenge in any organisation and managing the workload allocation of autonomy seeking academic staff in a business school can be even more so. In this study, the researcher aimed to review a recently designed and implemented academic workload allocation model in a South African business school in order to establish whether the model and implementation system has been successful in contributing to actual and perceived fairness and equity in workload distribution amongst their academic staff. The researcher did this by using a sequential exploratory mixed methods approach, first reviewing documentary evidence, which informed the design of an online survey with the academic staff, followed by semi-structured interviews with a sample group. The study reveals that the model, and the way it was implemented and managed, failed to achieve its intended aims of increased equitable and fair workloads amongst academic staff. These implementation failures have resulted in negative consequences for the organisational culture. Staff satisfaction and engagement with the model, its implementation and management does not present positively in the findings of this study. In the South African context where there are very few studies related to academic workload allocation models, the results of this study may be valuable for higher education institutions considering the introduction or review of workload models amongst their academic staff. The study highlights the importance of an inclusive and careful design approach, change management considerations during the implementation phase, and the transparent management of the workload allocation process and results.